Optimalisasi Potensi Agrowisata Cepoko Melalui Pendekatan SWOT: Strategi Peningkatan Kekuatan Dan Pengelolaan Ancaman - Agustina, Sofyya; Azizah , Rizky Annisa; Mila, Zamilatul; Azzahra, Alfiana Nur; Wardani, Endah Kusuma (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to explore the potential, obstacles, and development strategies of Cepoko Agrotourism in Gunungpati District, Semarang City. Cepoko Agrotourism is an agricultural-based tourism area that offers fruit picking experiences and nature education for visitors. This study uses a qualitative method with a descriptive approach through interviews, observations, and documentation. Data were collected from managers, farmers, and visitors of Cepoko Agrotourism. The results of the study indicate that Cepoko Agrotourism has great potential in developing agricultural-based tourism with more than 1,000 plants from 15 different types. The main supporting factors are active community participation, adequate facility support, and cooperation with the Department of Agriculture. However, this study also identified several obstacles such as the absence of a permanent market for crops, limited innovation in processing agricultural products, and seasonal conditions. Through a SWOT analysis, it was found that the main strength of Cepoko Agrotourism lies in its strategic location and the attraction of rare fruits. However, the main weaknesses are the lack of innovation in processing crops and the use of chemicals in agriculture. This study suggests development strategies in the form of innovation of processed fruit products, making green houses, using prepaid systems, and profit sharing systems between farmers and the Department of Agriculture to improve economic performance and sustainability of agrotourism.